Perancangan User Experience Aplikasi Pembayaran Berbasis Mobile Pada Usaha TV Kabel Menggunakan Pendekatan Human Centered Design (Studi Kasus: Linda Cable) - Widya Agusty Bintari; Hanifah Muslimah Az-Zahra; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Linda Cable is a growing privately-owned business located in Trenggalek District specializing in cable television service. With their increasing popularity, LindaCable still use physical records to keep track of their customer's monthly subscription bills. Seeing as they have two methods of payment: at home paymentwith the help of collectors or payment at Linda Cable office, the upkeep of physical records become increasingly difficult and time consuming not to mention the worry of human errors. To tackle this problem a dedicated mobile application is a practical solution offering mobility and efficiency in keeping up with customers' monthly billing. One of the most important aspect of application development is the User Experience design. To create said User Experience a method called HumanCentered Design is used so that user and stakeholder needs can both be covered. Usability testing covering effectivity and efficiency aspect of the design solutionshowed the design solution has a 100% efficiency rate with 0,20 goals/sec time based efficiency and 100% effectivity. The user satisfaction score, established with the help of SUS questionnaire, has a score of 70 which indicates the solution is in a â€œgoodâ€ category.